Sub-optimal nutrient regime coupled with Bacillus and Pseudomonas sp. inoculation influences trichome density and cannabinoid profiles in drug-type Cannabis sativa - Tanney, Cailun A. S.; Lyu, Dongmei; Schwinghamer, Timothy; Geitmann, Anja; Ruan, Eric D.; Smith, Donald L. (Frontiers in Plant Science, 2023)
Cannabis sativa remains under heavy legal restriction around the globe that prevent extensive investigations into agricultural applications for improving its development. This work investigates the potential of specific plant growth-promoting rhizobacteria (PGPR) to improve Cannabis yield through increased trichome densities on floral organs, and to determine if sub-optimal environmental conditions would affect the outcomes of PGPR presence by altering plant development and cannabinoid profiles. Here, Pseudomonas sp. or Bacillus sp. were applied to the root system either separately or in a consortium to determine the effect of this bacterial treatment on the density of stalked glandular trichomes. Further, a low nutrient regime was applied for the first half of plant development to determine if an environmental stressor interacts with the effects of the microbial treatments on stalked trichome densities. Following 8 weeks of flower development, trichome density on calyces and bracts of inflorescences were determined microscopically. Our findings unexpectedly indicate that recommended nutrient levels were linked to a decreasing trend in trichome densities with PGPR inoculations, but a low nutrient regime coupled with PGPR treatment increases them. Cannabinoid content is partially consistent with these results, in that a low nutrient regime increased the abundance of key cannabinoids compared to recommended regimes, with Bacillus sp. inoculation leading to the greatest number of significant changes between the two nutrient regimes. Overall, this work provides insight into how PGPR presence affects Cannabis stalked trichome development and cannabinoid profiles, and how environmental stressors can affect, and even enhance, trichome densities and influence major cannabinoid production, thereby pointing towards avenues for lowering the amount of chemical inputs during plant production without compromising yield.